Block-equal QRS decomposition of mimo channels with ML-based block successive cancellation detection - Dan Fang; Anzhong Wong; Jian-Kang Zhang; Kon Max Wong (SPAWC : signal processing advances in wireless communications, 2014)
The multiple-input and multiple-output (MIMO) channel model is very useful for the presentation of a wide range of wireless communication systems. This paper addresses the joint design of a precoder and a receiver for a point-to-point MIMO channel model in a scenario in which perfect channel state information (CSI) is available at both ends. We develop a novel framework for the dual transmission-reception process. Under the proposed framework, the receiver decomposes the channel matrix by using a block QR decomposition, where Q is a unitary matrix and R is a block upper triangular matrix. The optimal maximum likelihood (ML) detec- tion process is employed within each diagonal block of R. Then, the detected block of symbols is substituted and subtracted sequentially according to the block QR decomposition based successive cancellation. On the transmitting end, the expression of probability of error based on ML detection is chosen as the design criterion to formulate the precoder design problem. This paper presents a design of MIMO transceivers in the particular case of having 4 transmitting and 4 receiving antennas with full CSI knowledge on both sides. In addition, a closed-form expression for the optimal precoder matrix is obtained for channels satisfying certain conditions.